Teaching short prose works by N. Akish as the basis for the formation of national values of the child's personality (Journal of Educational Sciences, 2023)
In this article, the story “Where is the real grandma?” by N. Akhysh in the 5th grade Kazakh literaturetextbook is analyzed from a methodological point of view and the problem of teaching based on nationalvalues is considered. In the work family values are clearly revealed and subgroup names are based onnational names as well. In order to make the lesson interesting according to age characteristics, first ofall, by playing games, it is connected with the items used by grandmas when tasks are given. Accordingto the phrase of recognizing the meaning during the lesson, the tasks related to revealing the image ofthe characters in the story and evaluating them in comparison with life are also connected with conceptsclose to national knowledge. Working with the text, effective and new methods to reveal the image ofthe characters are thoroughly considered. It has been proven that a granny’s image can be fully revealedusing the “clamp method”. By choosing the national clothes worn by grandmothers, such as kamzol, shapan,waistcoat, kimeshek, jewelry it is studied how the writer can help learners find the image of a realgrandmother that the characters are looking for. Techniques to give importance to the author’s opinionand give learners the opportunity to express their own critical opinion are rationalized. Methods associatedwith national dishes such as Nauryz kozhe and shelpek also greatly contribute to the achievementof the lesson’s aim. The main thing is that the obtained methods are not only based on national valuesbut also contribute to national education. Approbation of the methods was carried out in the gymnasiumnamed after M.Makataev No. 140 in Almaty, 58 schoolchildren participated in the work.Key words: teaching methodology; method; national values, critical thinking, national dress, skills;modern Kazakh stories.